DAPUR SEHAT ANTI STUNTING MELALUI PEMBERDAYAAN KELUARGA BERBASIS MINI FARM LAYER - Umianita Risca Wulandari; Dian Kumalasari; Denis Melati (Jurnal Abdi Masyarakat, 2025)
Abstract: Stunting remains a priority issue for maternal and child health. Stunting issues, from district, provincial, and national levels, are always a major topic of discussion, including in Wonorejo Village, Kediri Regency. One of the community service partners is a Wonorejo village resident who is also a pilot project for stunting management. Providing information on stunting, training in raising laying hens with a mini-layer farm, training in making processed foods from chicken eggs, training in packaging and marketing processed food products can be alternatives to addressing stunting. The method applied starts from preparation including licensing and coordination, purchasing materials, and then the implementation stage which is divided into three activities. After that, monitoring and evaluation of the implemented program are carried out. The results of this community service activity are an increase in knowledge to good by 93% and partners are able to raise chickens with a mini-layer farm, make processed foods from eggs, and are able to package and market processed food products. Furthermore, it is hoped that the sustainability of the program will continue to be monitored.